Editorial: Regional responses to Higher Education world-wide challenges - Luigi F. Donà dalle Rose; Anna Serbati (Universidad de Deusto, 2017)
In this Issue we present firstly the answers given so far by Latin America to the challenge of Quality Assurance, with an eye to the perspective involved in a possible forthcoming transition to a second generation of QA programs. We then present a "sub-regional" spinoff effect of the AHELO project, involving higher education institutions of Japan and Indonesia, willing to test, with an appropriate tool, the achieved learning outcomes of their students of mechanical engineering (master level). Finally, we present three articles from three African countries - Morocco, Ethiopia, and Tanzania - which deal with different facets of the complex challenge of the relationship between higher education and job market, here inflected in terms of job access, graduates' wages, employability and actual employment after a competence-based learning path. The last article in this Issue, focused on a specific aspect of the above landscape of answers to major challenges, investigates the relationship between algebraic competences with emotional intelligence. First published online: 30 November 2017